3y-2z=5

Add 2z to both sides of the equation.

3y=5+2z

Divide each term in 3y=5+2z by 3.

3y3=53+2z3

Cancel the common factor of 3.

Cancel the common factor.

3y3=53+2z3

Divide y by 1.

y=53+2z3

y=53+2z3

y=53+2z3

Solve for y 3y-2z=5

Skip to content
# Solve for y 3y-2z=5

3y-2z=5

Add 2z to both sides of the equation.

3y=5+2z

Divide each term in 3y=5+2z by 3.

3y3=53+2z3

Cancel the common factor of 3.

Cancel the common factor.

3y3=53+2z3

Divide y by 1.

y=53+2z3

y=53+2z3

y=53+2z3

Solve for y 3y-2z=5